RANCANG BANGUN APLIKASI PELAYANAN KEBIDANAN BERBASIS WEB DENGAN METODE OOP (OBJECT ORIENTED PROGRAMMING) PADA PRAKTIK MANDIRI BIDAN NY.SARI - Erlin Nur Fatma; Crismantoro Budi Saputro; Irmawati Mathar (JRMIK, 2023)
The application of Information Technology in the field of Health has penetrated the obstetric sector. Butin reality there are still obstetric practices that have not had a positive impact on advances ininformation technology, one of them is the Ny.Sari’s Obstetric Clinic which in its service activities stillapplies a manual system and often encounters obstacles such as the difficulty of finding old patientdata, obstetric care documentation that meets storage, and report recapitulation takes a long time. Thegoal of this research is to develop a web-based midwifery service application that is expected tofacilitate the activities of midwifery services in the independent practice of Ny.Sari’s Obstetric Clinicmore effectively. The method used is OOP (Object Oriented Programming) method with UML (Unifiedmodeling Language) modeling to design Use Case Diagrams, Activity Diagrams, Class Diagrams, andSequence Diagrams. The stages of using the SDLC (System Development Life Cycle) method start fromthe requirement analysis, design, development, implementation and testing. The web-based obstetricsservice application requirements consist of the actors requirement, functional requirement, and nonfunctionals requirement. The results of the design of obstetric service application are currently madeattractive user interface design to facilitate the operation and implemented in the form of a website thatconsists of login menu, Dashboard, patient menu, service menu, queue menu and report menu. Withthe application of this obstetric service, service activities at Ny.Sari’s obstetric clinic become easier andmore effective